Limited Mentoring Resources Hinder PROPER Compliance in Pasuruan Regency: Sumber Daya Pembimbingan yang Terbatas Menghambat Kepatuhan terhadap PROPER di Kabupaten Pasuruan - Suhartati, Dana; Choiyirah, Ilmi Usrotin (Indonesian Journal of Public Policy Review, 2025)
General Background: Sustainable development mandates that corporations prioritize environmental stewardship, necessitating policy instruments like PROPER to promote performance beyond regulatory compliance. Specific Background: The Environmental Service of Pasuruan Regency (DLH) is tasked with providing mandatory assistance to companies participating in the PROPER program. Knowledge Gap: The actual effectiveness of this local PROPER mentoring, especially under resource constraints, remains underexplored using formal organizational effectiveness models. Aims: This study aims to analyze the Effectiveness of the PROPER Mentoring Program at the DLH Pasuruan Regency, employing M. Richard Steers' indicators: Goal Achievement, Integration, and Adaptation. Results: Goal Achievement faces significant obstacles due to a severe imbalance between the number of mentors and 50 participating companies. Conversely, Integration efforts are proactive in aligning goals and Adaptation involves active technical guidance. Novelty: This research distinctly identifies the critical constraint of human resource availability as the main barrier to achieving beyond compliance targets within the PROPER system at the regional level. Implications: To maximize effectiveness, DLH Pasuruan must urgently address the personnel gap, potentially through technology or non-technical staff mobilization, to ensure intensive mentoring and better goal attainment. Highlights Mentor-to-company ratio is severely imbalanced, hindering intensive assistance. Limited human resources directly compromise Goal Achievement and Adaptation indicators. The Environmental Service proactively demonstrates integration by aligning its goals for compliance. Keywords: Environmental Performance, Mentoring, PROPER, Resource Constraint, Steers Model.